STUDENTS’ PERCEPTIONS TOWARD THE IMPLEMENTATION OF GOOGLE APPS FOR EDUCATION DURING PANDEMIC - Asmara, Rekha -; Rafli, Zainal; Iskandar, Ifan (Universitas Muhammadiyah Surakarta, 2023)
This article focused on analyzing the students’ perceptions toward the implementation of Google Apps for Education (GAFE) during pandemic, namely; Google Classroom, Google Meet, and Google Form. A descriptive qualitative research method was applied with twelve undergraduate students majoring English field at Islamic University of Ogan Komering Ilir (UNISKI) Kayuagung taken as the research participants. To collect the data, the participants were asked to respond on the statements within the questionnaire. Likert Scale was then used. Findings showed that students gave positive perceptions regarding to the implementation of Google Apps for Education (GAFE) in online learning during the pandemic era. Most of the statements revealed that most students perceived positively their experience in learning online through the use of GAFE proposed in this study. Artikel ini berfokus pada analisis persepsi siswa terhadap implementasi Google Apps for Education (GAFE) selama pandemi, yaitu; Google Classroom, Google Meet, dan Google Form. Metode penelitian kualitatif deskriptif diterapkan dengan dua belas mahasiswa sarjana jurusan bahasa Inggris di Universitas Islam Ogan Komering Ilir (UNISKI) Kayuagung diambil sebagai peserta penelitian. Untuk mengumpulkan data, para peserta diminta untuk menanggapi pernyataan dalam kuesioner. Likert Scale kemudian digunakan. Hasil penelitian menunjukkan bahwa siswa memberikan persepsi positif terkait penerapan Google Apps for Education (GAFE) dalam pembelajaran daring di era pandemi. Sebagian besar pernyataan mengungkapkan bahwa sebagian besar siswa merasakan secara positif pengalaman mereka dalam belajar online melalui penggunaan GAFE yang diusulkan dalam penelitian ini.